2008
DOI: 10.1177/230949900801600313
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Ewing's Sarcoma: A Review from Scottish Bone Tumour Registry

Abstract: Intense multi-agent neo-adjuvant chemotherapy including ifosfamide followed by wide excision and postoperative radiation are recommended. Local therapy should not take precedence over or interfere with systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…A total of 288 (22.1%) patients with Ewing sarcoma were included in the current analysis, with a 5‐year survival rate of 46%. The earlier reports on pelvic Ewing sarcoma reported survival rates only as high as 20% to 30% 32, 34. We believe that improvement in survival among patients over the past 2 decades can be attributed to improvements in multimodal therapy for Ewing sarcoma and radiological imaging.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A total of 288 (22.1%) patients with Ewing sarcoma were included in the current analysis, with a 5‐year survival rate of 46%. The earlier reports on pelvic Ewing sarcoma reported survival rates only as high as 20% to 30% 32, 34. We believe that improvement in survival among patients over the past 2 decades can be attributed to improvements in multimodal therapy for Ewing sarcoma and radiological imaging.…”
Section: Discussionmentioning
confidence: 72%
“…The clinician is thus left wondering whether a uniform treatment strategy should be applied to all the patients regardless of the histopathology, as previously suggested, or each disease should be treated as a separate entity 1. An example of such a controversy is illustrated in the treatment recommendations for pelvic Ewing sarcoma, in which some authors have suggested considering radiotherapy as an alternative to surgery in pelvic Ewing sarcoma,30‐34 whereas others have stressed the importance of wide excision of the primary disease for this and other sarcomas 25, 35‐43…”
mentioning
confidence: 99%
“…It occurs most commonly during the second decade of life. 5 Treatment includes neoadjuvant chemotherapy in association with surgery and/or radiation therapy. It is located most frequently at the pelvis or the femur.…”
mentioning
confidence: 99%
“…Pelvis is the most common sites for Ewing's sarcoma, but the prognosis is much poorer than those at other sites, because of lack of main anatomical barrier against dissemination of the tumor, difficult for local treatment due to many surrounding organs and neurovascular bundles, and more common recurrence than other sites [11]. However, Puri et al recommended aggressive surgical treatment for nonmetastatic Ewing's sarcoma at pelvic bone, because surgical resection as much as possible can lower local recurrence rates and provides excellent functional results, only if tumor resection margin is thought to be able to get obtained through preoperative imaging studies [12].…”
Section: Discussionmentioning
confidence: 99%